A COMPARATIVE ANALYSIS OF SÃKÃ“Ì£ AND NÃÃNLÃ AS OCCURRING IN IFEÌ£Ì€ DIALECT AND THEIR VARIANTS, NÌKÃ“Ì£ AND NÌLÃ IN STANDARD YORÃ™BÃ LANGUAGE - Adekunle, Moses AdÃ©dire (IJOLTL (Indonesian Journal of Language Teaching and Linguistics), 2023)
This study focuses on the descriptive modeling of Chomskyan linguistic analysis on sÃkÃ³Ì£ and nÃÃnlÃ¡ as occurring in Ife dialect of Yoruba language in variance with nÌkÃ³Ì£ and nlÃ¡ in the standard Yoruba. We argue that the basic form of nÌ in nÌlÃ¡ and nÌkÃ³Ì£ is Ãn which is still traceable through sÃkÃ³Ì£ or sÃnkÃ³Ì£ and nÃÃnlÃ¡ in IfeÌ£ dialect of YorubÃ¡ language. We present the basic phonetic features of Ãn as in: vowel, high, syllabic, nasal and front. The lost of vowel, front and high features produces the orthographical representation of n in nÌlÃ¡ and nÌkoÌ£ in the standard Yoruba. Our findings therefore, serve as a solution to one of the fundamental issues in the grammar of Yoruba language which intuitively does not allow consonant cluster in syllabic formation. The language basically does not endorse a high tone to be the first syllable of a word with VCV sequence. Keywords: feature stability, syllabicity, grammaticalization, extension phrasal interaction and decategorization.